Minimally-invasive LVAD Implantation: State of the Art - S. Hanke, Jasmin; V. Rojas, Sebastian; Avsar, Murat; Haverich, Axel; D. Schmitto, Jan (Current Cardiology Reviews, 2015)
Nowadays, the worldwide number of left ventricular assist devices (LVADs) being implanted per year is higher than the number of cardiac transplantations. The rapid developments in the field of mechanical support are characterized by continuous miniaturization and enhanced performance of the pumps, providing increased device durability and a prolonged survival of the patients. The miniaturization process enabled minimally-invasive implantation methods, which are associated with generally benefitting the overall outcome of patients. Therefore, these new implantation strategies are considered the novel state of the art in LVAD surgery. In this paper we provide a comprehensive review on the existing literature on minimally-invasive techniques with an emphasis on the different implantation approaches and their individual surgical challenges.
Keywords: Minimal-invasive surgery